Fokozott hivatalnoki felelősség a gyermekek jogainak védelme érdekében a római jogban : Az örökösök felelőssége a magistratusok gyámrendeléséért - Újvári, Emese (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
In Ancient Rome, if a child was not under patria potestas, he needed a guardian to manage his property. While in the archaic period guardianship was essentially in the interests of the guardian, there was a gradual change in attitude, with the interests of the ward becoming more and more important. Accordingly, a growing number of legal instruments have been developed to prevent the embezzlement of the assets entrusted to the guardian and to enable the guardian to be prosecuted as effectively as possible in the event of such embezzlement. It is part of this development that in some cases the ward has been able to take action not only against the guardian who has mismanaged or embezzled the ward’s assets, but also against a certain number of officials responsible for the appointment of guardians. Moreover, in certain cases, it was not only the officials who were liable, but also the pater familias of the officials; or even their heirs in the event of the death of the magistratus. This latter possibility, however, was (again) the result of a lengthy process. The present study examines the causes and the dogmatic background of this process.